Edukasi Dampak Dari Media Sosial Dan Game Online, Terhadap Akhlak Siswa Di Sd Inpres Kapopo - Umar, Rukhayati; Dirga; Azmi; Rahmat; Ahmad; Awil; Abid (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2024)
social media and online games have become commonplace in the world of students, some of the benefits that can be obtained if done appropriately and correctly are that students' enthusiasm for learning increases, so that the learning outcomes obtained by students also increase, apart from that, the negative impact is of course that students become lazy about studying, concentration becomes increasingly difficult, especially students will be lazy about going to school and this will have an impact on the learning outcomes obtained which will decrease. Likewise, what happens to students at SD Inpres Kapopo, if done excessively, students cannot control their emotions. This is characterized by feeling restless and irritable if you are not allowed to play, regardless of the circumstances around you. For this reason, support and assistance is needed, if something negative happens, the impact of excessive use of social media and online games. By combining educational approaches, campaigns and collaboration with the community, this service can provide real benefits for students, parents and educators at SD Inpres Kapopo